Exploring the motives to participate in the sharing economy. Case Airbnb. - Antila, Roosa (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Sharing economy as a phenomenon has encountered major growth within the recent years. Consumers are increasingly keen in participating in different sharing economy services as owning is decreasing its importance and people prefer to share and gain experiences by accessing. The rise of sharing economy can be explained by multiple factors. Firstly, the global financial crisis has encouraged people to find alternative ways to consume. Secondly, people are increasingly reluctant in owning and attaching, since it doesn’t fit the modern consumer’s fast-moving and flexible lifestyle. Thirdly, major technological development has enabled sharing economy services to flourish by connecting people more broadly than ever before. Especially, the rise of the Internet has helped to overcome barriers such as transaction costs, trust and reputational factors that have once limited sharing activities. Even though the rise of sharing economy is clearly justifiable, there is still a lack of understanding why consumers participate in sharing. Therefore, this research aims to contribute in the understanding of consumers motives in taking part in sharing economy services, especially in peer-to-peer sharing. The research question was answered with the theoretical framework introduced in the research as well as conducting an empirical case study. The theoretical framework consists of sharing economy, motive and sharing behavior theories. The empirical data was collected by ten semi-structured thematic interviews with Airbnb users. Since the aim of this study was to gain understanding of the motives of both participants, providers and users, both sides were interviewed. The data collection was limited to Finnish users and host’s that hosted in Southern Finland. When discussing the motives to participate in sharing economy financial and social motives repeatedly rose. Additionally, experience and trend orientation acted as a motive especially for guests. The main conclusions of this study demonstrate that participants of P2P sharing platforms are motivated by various factors, which may differ in priority and emphasis. The findings clearly demonstrate, that providers balance between social and financial motives, which shouldn’t be seen as crowding out each other, but rather as supporting each other in forming a holistic motivation. Additionally, cost-utility relation as well as personal values were found to drive sharing behavior. This research demonstrates that values can explain the consumer’s attitudes towards a purchase decision and act as a driver for action, since it is found that sharing is strongly driven by values.

Jakamistalous ilmiönä on kasvanut huimasti viime vuosien aikana. Kuluttajat ovat yhä halukkaampia osallistumaan erilaisiin jakamistaloudenpalveluihin, kun asioiden omistaminen vähentää merkitystään. Jakamistalouden kasvua selittää moni tekijä. Ensinnäkin, maailmanlaajuinen talouskriisi on kannustanut ihmisiä löytämään vaihtoehtoisia kuluttamistapoja. Toisekseen, asioiden omistaminen ei välttämättä sovi modernin kuluttajan joustavaan ja nopeatahtiseen elämäntyyliin. Kolmannekseen, teknologian kehittyminen yhdistää kuluttajat keskenään laajemmin ja helpommin kuin koskaan ennen, joka on edesauttanut jakamistalouden palvelujen syntymistä. Etenkin Internetin kehittyminen on auttanut ylittämään tiettyjä esteitä, jotka ovat ennen rajoittaneet jakamista, kuten maksujen hoitamisen ja luottamuksen rakentamisen. Vaikka jakamistalouden kasvu on ilmeisen perusteltua, on silti hieman epäselvää miksi kuluttajat ovat halukkaita osallistumaan jakamistalouteen. Täten tämän tutkimuksen tavoite on selventää ja edistää ymmärrystä siitä, mikä motivoi kuluttajia osallistumaan jakamistalouden palveluihin, etenkin ihmisten keskinäisiin jakamisalustoihin (P2P-jakaminen). Tutkimuskysymykseen vastattiin sekä tutkimuksen teoriaosassa esitetyn aikaisemman tutkimuksen läpikäynnillä sekä empiirisen tapaustutkimuksen avulla. Teoreettinen viitekehys koostuu jakamistalouden, motivaation sekä jakamiskäyttäytymisen lähestymistavoista. Empiirinen tutkimus toteutettiin tekemällä kymmenen puolistrukturoitua teemahaastattelua Airbnb-käyttäjien kanssa. Tutkimuksen tavoite on ymmärtää molempia osallistujapuolia, käyttäjiä sekä tarjoajia, joten molempia osapuolia haastateltiin. Datan keräys rajattiin suomalaisiin käyttäjiin ja Etelä-Suomen alueella isännöiviin Airbnb-tarjoajiin. Motiiveista keskustellessa haastatteluissa nousivat vahvasti esille sosiaaliset sekä taloudelliset motiivit. Näiden lisäksi, etenkin käyttäjien haastatteluissa tärkeäksi nousivat kokemus- sekä trendiorientoituminen. Tutkimuksen tulokset osoittavat, että P2P-jakamisalustoihin osallistumisen taustalla on monia motiiveja, jotka vaihtelevat painotukseltaan sekä tärkeysjärjestykseltään. Tulokset indikoivat selkeästi tarjoajat tasapainottelevan sosiaalisten ja taloudellisten hyötyjen välillä, joiden ei pitäisi nähdä poissulkevan vaan lähinnä tukevan toisiaan, muodostaen kokonaisvaltaisen holistisen motivaation. Näiden lisäksi kustannus-hyöty -suhteen sekä arvomaailman nähtiin vaikuttavan jakamiskäyttäytymiseen. Arvomaailma voi selittää kuluttajien asenteita jakamispalveluita kohtaan ja näin toimia myös osallistumisen selittäjänä.